Draft Annual Plan 1982-83 Volume I Government of Jammu and Kashmir - Planning Commission (Planning Commission, 1981)
The Annual Plan for 1981 -82, second year of the Five Year Plan, 1980-85, was approved at Rs. 1 60,00.00 lacs which is 17.7$ of the Five Year Plan outlay. The anticipated expenditure is however put at Rs. 19210.8 lacs. The increase in expenditure over outlay will mainly be under Irrigation, Flood Control, Power, Industries, Roads and Bridges, General Education, Medical Education Water Supply and Public Works .The increase in expenditure has been, necessitated by the fact that adequate provisions could not be made .at the tine of plan formulation in case of important complete as per schedule. The marginal step-up provided could hardly cover the cost escalation. The absorption capacity in the State has considerably improved as a result of various measures taken in building proper infra-structure and introduction of 'de-centralization of Planning process.
Government of Jammu and Kashmir
Planning and Development Department Jammu
Keywords: Agriculture; Priority sector; Horticulture; Animal and Sheep Husbandry; The Cooperative sector; Command Area Development; Forests; Conservation measures; Minor source of irrigation; Irrigation project; Communication on road network; Power